Implementation of Competency-Based Job Training Programs in Community Empowerment at the Tulungagung Regency Manpower and Transmigration Office - Aditya Satria Wijaya (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to analyze the implementation of competency-based job training programs as a community empowerment effort at the Tulungagung Regency Manpower and Transmigration Office. The research focused on two types of programs: Competency-Based Job Training for Tobacco Excise Revenue Sharing Funds and Job Training Programs to Expand Employment Opportunities. The study used a descriptive qualitative approach with primary data sources obtained through direct observation during internships and a review of internal agency documents. Data analysis was conducted using Human Capital Theory to view job training as a process of improving skills, knowledge, productivity, job readiness, job opportunities, and adaptability to the job market. The results showed that both training programs contributed positively to improving participant competency, particularly in the aspects of job skills and job readiness. However, the impact of the training tended to be strong in the implementation and short-term phases, while post-training sustainability still faced limitations, particularly in terms of workforce absorption and independent business development. The DBHCT-based program was more oriented towards specific competencies in the service sector, while the job expansion program was more inclusive and functioned as a strengthening of the community's basic economy. These findings indicate that job training plays a strategic role in regional human resource development, but requires continued support to achieve a sustainable impact.